The expansion of endoscopic submucosal dissection in France: A prospective nationwide survey. Issue 1 (1st February 2017) - Barret, Maximilien; Lepilliez, Vincent; Coumaros, Dimitri; Chaussade, Stanislas; Leblanc, Sarah; Ponchon, Thierry; Fumex, Fabien; Chabrun, Edouard; Bauret, Paul; Cellier, Christophe; Coron, Emmanuel; Bichard, Philippe; et al.
Abstract : Introduction: Early reports of endoscopic submucosal dissection (ESD) in Europe suggested high complication rates and disappointing outcomes compared to publications from Japan. Since 2008, we have been conducting a nationwide survey to monitor the outcomes and complications of ESD over time. Material and methods: All consecutive ESD cases from 14 centers in France were prospectively included in the database. Demographic, procedural, outcome and follow‐up data were recorded. The results obtained over three years were compared to previously published data covering the 2008–2010 period. Results: Between November 2010 and June 2013, 319 ESD cases performed in 314 patients (62% male, mean (±SD) age 65.4 ± 12) were analyzed and compared to 188 ESD cases in 188 patients (61% male, mean (±SD) age 64.6 ± 13) performed between January 2008 and October 2010. The mean (±SD) lesion size was 39 ± 12 mm in 2010–2013 vs 32.1 ± 21 for 2008–2010 ( p  = 0.004). En bloc resection improved from 77.1% to 91.7% ( p  < 0.0001) while R0 en bloc resection remained stable from 72.9% to 71.9% ( p  = 0.8) over time. Complication rate dropped from 29.2% between 2008 and 2010 to 14.1% between 2010 and 2013 ( p  < 0.0001), with bleeding decreasing from 11.2% to 4.7% ( p  = 0.01) and perforations from 18.1% to 8.1% ( p  = 0.002) over time. No procedure‐related mortality was recorded. Conclusions: In this multicenter study, ESD achieved high rates of en bloc resection with a significant trend toward better outcomes over time. Improvements in lesion delineation and characterization are still needed to increase R0 resection rates.